Diabetes mellitus influences Toll-like receptors 2 and 4 in experimental apical periodontitis of Wistar rats - da Silva Machado, Nathália Evelyn [UNESP]; Segura-Egea, Juan José; Faria, Flávio Duarte [UNESP]; Cantiga-Silva, Cristiane [UNESP]; Ribeiro, Ana Paula Fernandes [UNESP]; Ervolino, Edilson [UNESP]; Matsushita, Doris Hissako [UNESP]; Estrela, Carlos; Cruz, Alvaro; Gomes Filho, João Eduardo [UNESP]; Araújo, Gustavo Sivieri [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Springer Nature, 2025)
The aim of this study was to investigate the inflammatory profile and immunostaining expression of Toll-like receptors 2 and 4 (TLR2 and TLR4) in periapical tissues of control and diabetic rats (DM) with induced apical periodontitis (AP), correlating these findings with the progression of root canal contamination. Forty male Wistar rats were divided into four groups: Group C—control rats, Group AP—rats with AP, Group DM—rats with diabetes, and Group DM + AP—rats with DM and AP. DM was induced using streptozotocin, and AP was induced by dental pulp exposure of the first mandibular molar to the oral environment. After 30 days, the jaws were removed and processed for histologic and bacterial analysis, as well as immunochemical assays for TLR2 and TLR4. Two-way analysis of variance was used (P < 0.05). Inflammatory infiltrate was moderate in the AP group and severe in the DM + AP group (P < 0.05). There was a greater presence of bacteria disseminated in the apical region in the DM + AP group when compared with the AP group (P < 0.05). TLR2 and TLR4 levels were significantly higher in the DM + AP group when compared to the AP group (P < 0.05). Diabetes increases the inflammatory infiltrate in AP, causing significant overexpression of TLR2 and TLR4 in the periapical inflammatory tissues of diabetic rats. By activating TLRs, diabetes exacerbates the immune response in AP, increasing inflammation and influencing the progression of bacterial contamination.